PERAN PETUGAS KESEHATAN DAN PENGETAHUAN KELUARGA TERHADAP PENINGKATAN KEMAMPUAN MERAWAT KLIEN GANGGUAN JIWA DI RUMAH - Edi Purnomo; Zulhaini Sartika A. Pulungan; Andi Milawati (Politeknik Kesehatan Kemenkes Mamuju, 2016)
Mental disorder schizophrenia is a disorder psychic who ranks second in diseases that cause the greatest burden after heart disease. Its burden of mental disorders is mainly felt by the families who have family members with mental disorders. Patients with mental disorders who live with the family does not always indicate the best condition for the recovery of the client. The purpose of this study was to determine the effect of the role of the clerk and the knowledge of the family in improving the ability of families caring for clients with mental disorders at home. This research method is descriptive quantitative research design descriptive analytic approach cross sectional study. The samples used were 30 families who have family members experiencing mental disorders withpurposivesampling method. The research was conducted in Puskesmas Ulumanda Majene district. Results showed no effect between family knowledge (p=0.005) and the role of health care workers (p=0.008) with the ability of families in caring for clients with mental disorders at home. Conclusion the role of health workers and knowledge affect the ability of families caring for clients with mental disorders at home. Advised the family to be more active in seeking information about the treatment of people with mental disorders at home and health officials often approach to the family to help care clients with mental disorders.